First description of the eggs of the Sumatran Partridge Arborophila sumatrana - Vladislav Marcuk; Sebastian van Balen; Donovan de Boer; Richard Noske (KUKILA, 2020)
The breeding biology of forest partridges (genus Arborophila) is poorly understood, with nest and eggs described for just over half of all 20 recognised species. Herein we provide the first formal description of the eggs of the endemic Sumatran Partridge, based on a single preserved clutch in the Naturalis Biodiversity Centre, Leiden. Information about clutch size, egg characteristics and breeding phenology for the Sumatran Partridge is consistent with the published data available for other members of the super-species from South-East Asia.